(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The following design paper reports on a serious game project being made by interdisciplinary researchers at the North-West University (NWU), Vanderbijlpark Campus. The aim of this venture is to develop a trading card game based on specific History content, using similar mechanics found in popular card games such as Magic: The Gathering and the Pokémon Trading Card Game. The game is called Dogs of War (DoW) and the historical figures will be depicted as various dog breeds to subvert player expectations and assuage a grim period of human History. The game itself is designed in such a way that up to six people can play together, with each player representing a faction that was involved in the war. These factions include: Nazi Germany, Imperial Japan, Fascist Italy, Great Britain, United States of America and Soviet Russia. The conceptualisation of DoW has already reached the initial play-testing phase, wherein the basic mechanics and units already having been designed. The game will be implemented in a third year History class at NWU in 2020, with the aim of researching whether the game itself can enhance self-directed learning through tangential and exciting gameplay. Focus group interviews will be held at the end of the first semester (2020) to gauge this prototype’s overall effectiveness.